Effect of Electrical Stimulation (ES) Combined with Conventional Therapy on Spasticity, Function and Ambulation for patients with stroke: Protocol for a Randomized Control Trial - Islam, Mohammad Mohinul; Sultana, Sharmin; Urme, Nadia Afrin; Sultana, Arifa; Hossain, Kazi Amran (British Journal of Healthcare and Medical Research, 2022)
Background: Spasticity is a motor symptom which is responsible for impairments as it decreases range of movement, postural abnormality, poor hygiene, inability to perform daily activities. Since the 1960s, electrical stimulation (FES) has been used to treat chronic hemiplegic patients. It is a physical therapeutic approach that improves spasticity by agonist muscle relaxation or antagonist muscle strengthening. This study aims to evaluate the effect of electrical stimulation along with conventional therapy and conventional therapy alone on spasticity, function and ambulation of the individuals suffering from Stroke. Method and analysis: The study will be a multicenter, Randomized Control Trial (RCT). Stroke survivors with spasticity in any limbs who will attend in the neurology unit of 24 selected rehabilitation centers including Center for the Rehabilitation of the Paralysed (CRP) Savar and Mirpur Dhaka, Bangladesh from July 2022 to February 2023, will be considered as study population. Hospital based randomization processes will be employed. To receive either conventional intervention or EFS along with conventional , participants will be randomly assigned into [1:1] groups. Concealed allocation will be executed by computer generated randomization and will be done by another person who is not involved in the trial. Primary outcome spasticity will be evaluated by modified Asworth grading scale and modified Tardieu scale; function by Barthel Index and ambulation by 10 meter walk test. Secondary outcome upper extremity muscle strength will be evaluated by motricity index and lower limb function by lower extremity functional scale (LEFS). Conclusion: FES with conventional therapy will add new knowledge to manage stroke patients. Reduction of spasticity and improvement of function will reduce the burden of stroke patients as well as their families. Hopefully this research will update the rehabilitation process of stroke patients in Bangladesh.